A Effect of Various Cooking Methods on Quality and Sensory Characteristics of Tempeh Made from Soybeans and Corn - Daimon Syukri; Diana Sylvi; Siska Fitri Ramadani (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
One variation of tempeh products is using corn. Tempeh made form soybeans with the addition of corn has obtained the best treatment with a ratio of soybean : corn namely (80 : 20)%. There is no research that discusses the character of soybean tempeh with the addition of corn during the processing. This study aims to determine the best cooking method (boiling, frying and steaming) for the quality and sensory characteristics of tempeh made from soybeans and corn. The ratio of soybean and corn used is (80;20)%. The research method used is an experimental method with descriptive analysis. The study was carried out with 4 treatments namely control, boiling tempeh at 100°C for 10 minutes, fryingat 162°C for 3 minutes, steaming at 90°C for 10 minutes, 3 replicates. Chemical analysis was carried out namely water content analysis, ash content, fat content, protein content, carbohydrate content, crude fiber content, total carotene and antioxidant activity of tempeh. Then the organoleptics test was carried out on the level of preference of the panelists on the parameters of aroma, color, taste and texture of tempeh. The results showed that the best cooking method was in treatment C, frying tempeh at a temperature of 162°C for 3 minutes with a moisture content of 41,33 %. Ash content of 1,43 %, fat content 33,60%, protein content of 17,80 %, carbohydrate content is 6,65%, total carotene is 7,67%, crude fiber contane is 5,75%, % inhibition is 23,85%. Sensory assessment of tempeh with several cooking methods, the most preferred, namely in treatment C (Frying at 162°C for 3 minutes) with aroma 4,25 (likes), color 4,20 (likes), taste 4,00 (likes)and texture 4,(30 likes).